Halenia coreana (Gentianaceae), a new species from Korea: Evidence from morphological and molecular data - Han, Su-Min; Won, Hyosig; Lim, Chae Eun (Phytotaxa, 2019)
A new species of Halenia (Gentianaceae) from Korea, H. coreana S.M.Han, H.Won & C.E.Lim, is recognized based on morphological and molecular data, and its description and illustration are provided. It is distinct from H. corniculata in having long, narrower and incurved spurs and attenuated leaf apex. Molecular sequence data of nuclear ribosomal ITS region, nuclear XDH gene, and chloroplast rbcL gene also strongly support its species status.